Testing variations within the Tagish Lake meteorite—II: Whole‐rock geochemistry of pristine samples. (June 2014) - Blinova, Alexandra I.; Herd, Christopher D. K.; Duke, M. John M.
Abstract Four pristine specimens of the Tagish Lake C2 chondrite meteorite were previously determined through mineralogy, petrology, and organic chemistry to have been affected by aqueous alteration in the order (from least to most altered) TL5b < TL11h < TL11i, and TL11v as a mixture of the other specimens (Herd et al. 2011; Blinova et al. 2014). Here, we report the whole‐rock data for a total of 65 elements for the same four Tagish Lake samples as determined by ICP‐MS and ICP‐AES (utilizing the Parr bomb digestion method on small samples, approximately 50 mg), and by INAA. Our data demonstrate that the determined aqueous alteration sequence has a positive correlation with trace elements, such as K and Br that are mobile during aqueous alteration, which appear to be controlled by an increase of phyllosilicates from least to most altered samples. Yet, the homogeneity of other elements suggests that elemental mass transfer occurred on a localized scale and aqueous alteration was isochemical for these elements, similar to other primitive carbonaceous chondrites. By plotting data from three samples (TL5b, TL11h, and TL11i) on a Zn/Mn versus Sc/Mn diagram, we also confirm that the Tagish Lake meteorite is not a simple mixture of CI and CM material.